User Perceptions of Academic Service Satisfaction at FKIP Sriwijaya University: SIMAK Version 3.0 - Riansih, Riansih; Sriati, M.S., Sriati, M.S.; Iriani, Atrika (Journal of Educational Sciences, 2025)
The rapid development of information technology encourages universities to adopt academic information systems to improve the efficiency and quality of educational services. Sriwijaya University uses the SIMAK system as an integrated academic management platform, but the implementation of version 3.0 at the Faculty of Teacher Training and Education (FKIP) still faces various technical and functional obstacles. This research discusses users' perceptions of the academic services provided by SIMAK Version 3.0 at FKIP Sriwijaya University. A descriptive qualitative approach was used with the theoretical basis of the Technology Acceptance Model (TAM), and data were obtained through in-depth interviews with students, lecturers, and education staff as active users of SIMAK. The results showed two main components that influence user perceptions, namely the ease of use of the system and perceived benefits, such as efficiency and faster access to academic information. These two factors contribute positively to the level of user satisfaction, although some obstacles such as system glitches, lack of notifications, and cumbersome technical procedures are still obstacles. This study recommends increased training, provision of clearer guidelines, and strengthening of system infrastructure to improve user acceptance and satisfaction with digital academic services.